3D finite-element modelling of soil arch shape in a piled embankment. Issue 3 (23rd August 2018) - Yang, Tao; Lu, Zhenrong; Ni, Jing; Wang, Ganggang
Abstract : Soil arching is a common phenomenon in a piled embankment. A precise soil arch shape is a key prerequisite for developing an analytical model to calculate the soil arching effect. In this study, a three-dimensional (3D) elastic–plastic finite-element model which simulates the formation process of soil arching in a piled embankment was established. The 3D shape of the soil arch in a piled embankment without reinforcements was investigated by the finite-element method. Then, a parametric study on the height of the soil arch was conducted. The results show that the soil arch in a piled embankment is a semi-ellipsoidal shape when 'maximum arching' is reached. The height of the soil arch is strongly affected by the clear spacing of the pile cap and the height of the embankment. The height of the soil arch increases gradually with increasing clear spacing of the pile cap. It increases with increasing the height of embankment to a certain value, and then remains constant beyond this critical embankment height. The value of the internal friction angle of the embankment fill has little effect on the height of the soil arch.